Emission inventory of non-methane volatile organic compounds from anthropogenic sources in India. (February 2015) - Sharma, Sumit; Goel, Anju; Gupta, Divya; Kumar, Atul; Mishra, Arabinda; Kundu, Seema; Chatani, Satoru; Klimont, Zbigniew
Abstract: This paper presents a new inventory of NMVOC emissions from anthropogenic sources in India for the year 2010. The main new element of this inventory, compared to previous work for India, is the use of new and more detailed data on solvent use sectors and oil production and distribution system. The results are presented at the national and state level for major sectors and VOC species. Finally, the annual emissions were spatially distributed at a fine resolution of 36 × 36 km 2 using detailed spatial information. The total anthropogenic NMVOC emissions in India in 2010 were estimated at 9.81 Tg which is in the range of the estimates made in most other studies. The majority of emissions (60%) originated from residential combustion of biomass for cooking. Solvent use sectors and oil production and distribution contributed about 20% followed by transport (12%) and open burning of agricultural residues (7%). Specie-wise distribution shows highest contribution from alkenes and alkynes (38%), followed by alkanes (22%), and aromatics (16%). Highlights: Latest multi-sectoral high-resolution NMVOC emission inventory of India. Inclusion of key sectors like solvents use and oil and gas handling. Anthropogenic NMVOC emissions in 2010 are estimated at 9.81 Tg. Residential, solvents, and transport sector contribute 60%, 16% and 12%, respectively. Major contribution from alkenes and alkynes (38%), alkanes (22%), and aromatics (16%).